Investigate The Social Cognitive Determinants of Physical Activity Participation Among Vaccinated Malaysians - Mohammad, Aminuddin bin; Tumijan, Wahidah binti (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
Physical inactivity is a global public health concern associated with various adverse health outcomes. The pandemic restrictions on outdoor activities have caused physical activity levels to decrease by 6.3% globally. After vaccination is introduced, many individuals may feel more confident and safer to engage in physical activities but no fixed percentage of increased physical activity participation. This study aims to measure the social cognitive determinants of physical activity participation among vaccinated Malaysians. A total of 372 respondents, who had received vaccinations, were recruited for this study. The participants were selected from different age groups and genders in Malaysia. Multiple linear regression analysis was conducted to measure the relationship between the social cognitive determinants and physical activity participation among vaccinated Malaysians. The results revealed a significant relationship between the social cognitive determinants and physical activity participation (β = 0.44, p < 0.001). Self-efficacy (β = 0.44, p = 0.001) was found to be a significant predictor of physical activity participation. Participants with higher levels of self-efficacy were more likely to engage in regular physical activity. Similarly, outcome expectations (β = 0.25, p = 0.039), and goals (β = 0.64, p = 0.001) were positively associated with physical activity participation. In contrast, sociostructural factors demonstrated a negative association with physical activity participation (β = -0.49, p = 0.001). In conclusion, this study provides valuable insight into the social cognitive determinants of physical activity participation among vaccinated Malaysians. Understanding the role of social cognitive determinants may provide insights into strategies to promote physical activity among this population.